Physical activity buffers fatigue only under low chronic stress - Strahler, Jana; Ditzen, Beate (Stress, 2016)
Fatigue is one of the most commonly reported complaints in the general population. As physical activity (PA) has been shown to have beneficial effects, we hypothesized that everyday life PA improves fatigue. Thirty-three healthy students (21 women, 22.8 ± 3.3 years, 21.7 ± 2.3 kg/m2) completed two ambulatory assessment periods. During five days at the beginning of the semester (control condition) and five days during final examination preparation (examination condition), participants repeatedly reported on general fatigue (awakening, 10 am, 2 pm, 6 pm and 9 pm) by means of an electronic diary, collected saliva samples for the assessment of cortisol and α-amylase immediately after providing information on fatigue and wore a triaxial accelerometer to continuously record PA. Self-perceived chronic stress was assessed as a moderator. Using hierarchical linear modeling, including PA, condition (control vs. examination), sex and chronic stress as predictors, PA level during the 15 min prior to data entry did not predict momentary fatigue level. Furthermore, there was no effect of condition. However, a significant cross-level interaction of perceived chronic stress with PA was observed. In fact, the (negative) relationship between PA and fatigue was stronger in those participants with less chronic stress. Neither cortisol nor α-amylase was significantly related to physical activity or fatigue. Our study showed an immediate short-term buffering effect of everyday life PA on general fatigue, but only when experiencing lower chronic stress. There seems to be no short-term benefit of PA in the face of higher chronic stress. These findings highlight the importance of considering chronic stress when evaluating the effectiveness of PA interventions in different target populations, in particular among chronically stressed and fatigued subjects.
Gesehen am 13.02.2018